Activation of AMPK reduces the co-transporter activity of NKCC1. (March 2014) - Fraser, Scott A.; Davies, Matthew; Katerelos, Marina; Gleich, Kurt; Choy, Suet-Wan; Steel, Rohan; Galic, Sandra; Mount, Peter F.; Kemp, Bruce E.; Power, David A.
Abstract The co-transporter activity of Na+-K+-2Cl− 1 (NKCC1) is dependent on phosphorylation. In this study we show the energy-sensing kinase AMPK inhibits NKCC1 activity. Three separate AMPK activators (AICAR, Phenformin and A-769662) inhibited NKCC1 flux in a variety of nucleated cells. Treatment with A-769662 resulted in a reduction of NKCC1T212/T217 phosphorylation, and this was reversed by treatment with the non-selective AMPK inhibitor Compound C. AMPK dependence was confirmed by treatment of AMPK null mouse embryonic fibroblasts, where A-769662 had no effect on NKCC1 mediated transport. AMPK was found to directly phosphorylate a recombinant human-NKCC1 N-terminal fragment (1–293) with the phosphorylated site identified as S77. Mutation of Serine 77 to Alanine partially prevented the inhibitory effect of A-769662 on NKCC1 activity. In conclusion, AMPK can act to reduce NKCC1-mediated transport. While the exact mechanism is still unclear there is evidence for both a direct effect on phosphorylation of S77 and reduced phosphorylation of T212/217.